Influence of melting mode on melt pool dynamics and microstructure in WE43 Mg alloy: A combined computational and experimental approach - Francesco D’Elia; Mohammad Hoseini-Athar; Satya Chaitanya Vaddamanu; Mikael Ersson; Peter Hedström; Cecilia Persson (Materials & Design)
In this study, laser-material interactions during laser-powder bed fusion of WE43 magnesium alloy were characterized through numerical and experimental analyses. Various melting modes (i.e., conduction, transition, and keyhole) were induced through deposition of laser tracks at powers ranging from 80 to 130 W, and used as input parameters for a thermo-fluid model. Results of microscopy demonstrated good agreement between numerical and experimental measurements of melt pool depth, as well as a strong correlation between melt pool microstructure and the thermo-fluid conditions predicted by the model. Specifically, for conduction mode at 80 W, a predominance of cellular subgrains within the melt pool was consistent with the predicted steep thermal gradients, while for keyhole mode at 130 W, low thermal gradients correlated with high presence of equiaxed dendrites. Moreover, convection currents attributed to high recoil pressure in keyhole melt pools, were in agreement with locations of numerous subgrain boundaries having non-uniform morphologies, while under conduction, outward Marangoni flow led to a unique alignment of cellular subgrains and fewer subgrain boundaries. This study demonstrates the interplay among processing, thermal history, fluid flow and microstructure in WE43, and provides a basis for future design of microstructures for improved material properties.